D4MD - Deformation system for a vehicle simulation game - Rodrigues, T.; Pires, R.; Dias, J. M. S. (ACE '05: Proceedings of the 2005 ACM SIGCHI International Conference on Advances in computer entertainment technology, 2005)
This paper presents a hybrid geometrical-physical, plastic deformation technique applicable for solids, in the context of a car simulation game. This technique doesn't aim to be mechanically correct but to produce visual appealing and realistic-looking results.